TIMM8B promotes oxidative phosphorylation and glycolysis by inhibiting the mtROS/ASK1/JNK signaling pathway in ovarian cancer - Yue Jia; Jiaqian Liao; Xiangqun Yang; Hongyan Hu; Wentao Zhao; Liufang Zhao; Conghui Ai; Yuanbo Xue; Shufen Tan; Yi Zhang (Biology Direct)
Abstract Background Ovarian cancer is a complicated and heterogeneous disease. In this study, we investigated the functional significance of the gene TIMM8B, which is differentially expressed in ovarian cancer to better understand the molecular processes involved in the development of this disease. Methods RNA sequencing was performed on ovarian cancer tissues and adjacent noncancerous tissues. The mRNA expression profiles obtained from the sequencing data (transcripts), TCGA-OV, and GSE14407 were subsequently used to identify common DEGs. GO, KEGG pathway, and PPI network analyses of these common DEGs were conducted. The expression of TIMM8B was examined in ovarian cancer tissues and cell lines. The effects of TIMM8B on cellular behaviors, such as proliferation, apoptosis, migration, invasion, and energy metabolism, were assessed by conducting cell-based assays. Additionally, the regulation of these processes by TIMM8B through the mtROS/ASK1/JNK signaling pathway was investigated. Results A total of 233 common DEGs were identified in ovarian cancer. The results of the GO analysis revealed enrichment in extracellular matrix organization, collagen-containing extracellular matrix, and transmembrane transporter activity, among others. The results of the KEGG pathway analysis revealed the involvement of DEGs in pathways such as oxidative phosphorylation and glycolysis/gluconeogenesis. TIMM8B was upregulated in ovarian cancer tissues and cell lines. TIMM8B enhanced oxidative phosphorylation, glycolysis, proliferation, migration, and invasion and inhibited apoptosis in ovarian cancer cells. TIMM8B was found to exert its effects through the suppression of mtROS/ASK1/JNK signaling. Conclusion TIMM8B may regulate the mtROS/ASK1/JNK pathways, leading to an increase in oxidative phosphorylation and glycolysis. Targeting TIMM8B and its associated signaling pathway may help in the development of new treatment approaches for ovarian cancer.